Coupled Gas Flow, Diffusion and Reaction in a ppb-level SnO2-NiO Formaldehyde Sensor System - Darcovich, K; Tunney, J; Dunford, J; Styles, L; Xiao, G; Constant, A (The International Journal of Multiphysics, 2011)
The present project is part of an effort towards the development of a ppb-level formaldehyde sensor system for indoor air quality. An electroceramic response model for a SnO2-NiO composite solid oxide sensing material of n-type conductivity inside the porous material is coupled with a transient flow field simulation of the delivery of a formaldehyde pulse to the sensor surface. Coupled volumetric CFD domains are used to examine the effects of the transport of formaldehyde from a preconcentrator unit to the sensor, and its implications for interpreting the sensor signals from laboratory experiments.